Current Anesthesia Management of Congenital Diaphragmatic Hernia: A Narrative Literature Review - Syukur, Rusmin Bolo; Elizeus Hanindito (HM Publisher, 2023)
Congenital diaphragmatic hernia (CDH) is a congenital disorder characterized by a defect in the diaphragm, which causes the contents of the stomach to protrude into the chest cavity. Increased survival of CDH patients related to initial management in the form of a ventilator strategy, management of pulmonary hypertension, improvement of surgical and anesthetic techniques, and use of extracorporeal membrane oxygenation (ECMO) when indicated. Early stabilization of the patient is a priority before performing a surgical intervention for the hernia organ. This narrative literature review aimed to explain the current management, especially in the field of anesthesia in a congenital diaphragmatic hernia. In conclusion, the current management aims to improve survival rates and reduce the morphology of CDH patients.